Transforming the Travel Experience: A Dynamic Marketing Approach Kinarya Jaya Tour & Travel - Satrio Sudarso (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2023)
Kinarya Jaya Tour & Travel is a tourism agency in Surabaya, Indonesia. The company is facing a significant decline in its operations and revenue during the COVID-19 pandemic due to travel restrictions and the closure of tourist attractions. To increase demand and interest in their services, the company needs to implement marketing strategies that are effective and relevant in the current era. To address the identified issues, the company should conduct a thorough evaluation of the current business model and develop a new business model to adapt to the changing government regulations. Different marketing strategies can be combined to create a comprehensive plan. These strategies may include SWOT analysis, Quantitative Strategic Planning Matrix (QSPM), Competitive Profile Matrix (CPM), Strategic Position and Action Evaluation (SPACE), and Business Model Canvas (BMC). Combining these approaches will help Kinarya Jaya Tour & Travel formulate an effective marketing strategy to improve its business performance. In addition, qualitative research methods, such as in-depth interviews, observations, and document studies, can be used to collect data for analysis. The use of triangulation can ensure the accuracy and credibility of the data. By using these strategies and conducting a thorough analysis, Kinarya Jaya Tour & Travel can create a comprehensive marketing plan that aligns with its goals and adapts to the ever-changing landscape of the tourism industry.